2020
DOI: 10.1158/2326-6066.cir-19-0556
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Early-Stage Myeloid-Derived Suppressor Cells in Cancer Requires Excluding Basophils

Abstract: Supplementary data -Supplementary Table S1 and Supplementary Fig. S1 Author contributions ANHK and BHS developed the study and wrote the manuscript. ANHK, TRE, EA, BS, and BHS designed and performed experiments and analyzed data. JTW performed morphological analysis and JM performed clinical data analysis. KHE oversaw the statistical analysis. KLS, TRE, JM, and JTW contributed to the manuscript preparation. JDT, KBM, KO, SIA, and BHS provided technical support and conceptual advice. All authors discussed the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…In addition to M–MDSCs and PMN–MDSCs, a third small population of MDSCs exhibiting promyelocytic appearance has been described in humans—immature or early-stage MDSCs, defined as CD33 + CD11b + HLA–DR − CD14 − CD15 − cells [ 4 , 8 ]. However, recent investigations have suggested that early-stage MDSCs defined by these surface markers include significant number of basophils [ 9 ]. Thus, further efforts will be required to define this MDSC subset.…”
Section: Mdsc Nomenclaturementioning
confidence: 99%
“…In addition to M–MDSCs and PMN–MDSCs, a third small population of MDSCs exhibiting promyelocytic appearance has been described in humans—immature or early-stage MDSCs, defined as CD33 + CD11b + HLA–DR − CD14 − CD15 − cells [ 4 , 8 ]. However, recent investigations have suggested that early-stage MDSCs defined by these surface markers include significant number of basophils [ 9 ]. Thus, further efforts will be required to define this MDSC subset.…”
Section: Mdsc Nomenclaturementioning
confidence: 99%
“…The immunosuppressive bone marrow microenvironment (BMME) in MM contains cellular elements that facilitate the immune evasion of malignant MM clones (9)(10)(11)(12)(13). These immunosuppressive cells include MDSCs, an immature myeloid cell population capable of inhibiting effector cytotoxic T-cell (CTL) populations as well as natural killer (NK) cells and contribute to the T-cell exhaustion which is a hallmark of the BMME in MM patients (4,(14)(15)(16)(17)(18)(19)(20). In addition, regulatory T cells (Tregs), regulatory B-cells (Bregs), and tumor-associated macrophages (TAM) also contribute to BMME-associated immunosuppression (20).…”
Section: Immunosuppressive Bone Marrow Microenvironment In Multiple Myelomamentioning
confidence: 99%
“…In contrast, there are currently no reports that mouse basophils express TrkA. Both human and mouse basophils share the expression of a variety of chemokine receptors (13,(51)(52)(53)(54)(55)(56), but it remains to be determined if mouse basophils express CCR1 and CXCR1 (57). These phenotypic comparisons between human and mouse basophils are summarized in Table 1.…”
Section: Proinflammatory and Immunoregulatory Mediators/cytokines Relmentioning
confidence: 99%
“…Peripheral blood basophils have also been associated with certain solid tumors ( 189 ). Basopenia appears to be associated with poor prognosis of colorectal cancer ( 190 , 191 ), whereas circulating basophils have no predictive role in breast cancer ( 192 ), ovarian cancer ( 54 ) and oral squamous cell carcinoma ( 193 ). Of note, high relative circulating basophils positively associated with improved outcome in melanoma patients undergoing immunotherapy with nivolumab plus ipilimumab ( 194 ).…”
Section: Peripheral Blood Basophils and Human Cancermentioning
confidence: 99%